Improving the recruitment activity of clinicians in randomised controlled trials: a systematic review - Fletcher, B; Gheorghe, A; Moore, D; Wilson, S; Damery, S (BMJ Publishing Group, 2012)
Background Poor recruitment to randomised controlled trials (RCTs) is a widespread problem. Provision of interventions aimed at supporting or incentivising clinicians may improve recruitment to RCTs. Objectives To quantify the effects of strategies aimed at improving the recruitment activity of clinicians in RCTs, complemented with a synthesis of qualitative evidence related to clinicians' attitudes towards recruiting to RCTs. Data sources A systematic review of English and non-English articles identified from: The Cochrane Library, Ovid MEDLINE, Ovid EMBASE, Ovid PsycINFO, Ebsco CINAHL, Index to Theses and Open SIGLE from 2001 to March 2011. Additional reports were identified through citation searches of included articles. Study eligibility criteria Quantitative studies were included if they evaluated interventions aimed at improving the recruitment activity of clinicians or compared recruitment by different groups of clinicians. Information about host trial, study design, participants, interventions, outcomes and host RCT was extracted by one researcher and checked by another. Studies that met the inclusion criteria were assessed for quality using a standardised tool, the Effective Public Health Practice Project tool. Qualitative studies were included if they investigated clinicians' attitudes to recruiting patients to RCTs. All results/findings were extracted, and content analysis was carried out. Overarching themes were abstracted, followed by a metasummary analysis. Studies that met the inclusion criteria were assessed for quality using the Critical Appraisal Skills Programme qualitative checklist. Data extraction Data extraction was carried out by one researcher using predefined data fields, including study quality indicators, and verified by another. Results Eight quantitative studies were included describing four interventions and a comparison of recruiting clinicians. One study was rated as strong, one as moderate and the remaining six as weak when assessed for quality using the Effective Public Health Practice Project tool. Effective interventions included the use of qualitative research to identify and overcome barriers to recruitment, reduction of the clinical workload associated with participation in RCTs and the provision of extra training and protected research time. Eleven qualitative studies were identified, and eight themes were abstracted from the data: understanding of research, communication, perceived patient barriers, patient-clinician relationship, effect on patients, effect on clinical practice, individual benefits for clinicians and methods associated with successful recruitment. Metasummary analysis identified the most frequently reported subthemes to be: difficulty communicating trial methods, poor understanding of research and priority given to patient well-being. Overall, the qualitative studies were found to be of good quality when assessed using the Critical Appraisal Skills Programme checklist. Conclusions There were few high-quality trials that tested interventions to improve clinicians' recruitment activity in RCTs. The most promising intervention was the use of qualitative methods to identify and overcome barriers to clinician recruitment activity. More good quality studies of interventions are needed to add to the evidence base. The metasummary of qualitative findings identified understanding and communicating RCT methods as a key target for future interventions to improve recruitment. Reinforcement of the potential benefits, both for clinicians and for their patients, could also be a successful factor in improving recruitment. A bias was found towards investigating barriers to recruitment, so future work should also encompass a focus on successfully recruiting trials.